MENAKAR EFEKTIVITAS PENYELESAIAN KREDIT MACET MELALUI GUGATAN SEDERHANA (Studi Kasus PT. Bank Perekonomian Rakyat Bhumikarya Pala Sleman) - Vania Valensia Firdaus; Itok Dwi Kurniawan (Sebelas Maret University, 2025)
This study aims to examine the effectiveness of resolving non-performing loans through the simplified lawsuit mechanism at PT BPR Bhumikarya Pala Sleman and to analyze the legal consequences arising from such legal action. Non-performing loans are a serious issue in the banking sector that can disrupt the bank’s operational stability, thus requiring a fast, simple, and efficient resolution. One alternative legal remedy is the simplified lawsuit, as regulated under Supreme Court Regulation (PERMA) No. 2 of 2015 in conjunction with PERMA No. 4 of 2019. This research employs an empirical approach, using data collection techniques through interviews and document analysis. Primary data were obtained through interviews with bank representatives, while secondary data were collected from legislation, legal literature, and relevant documents related to the settlement of non-performing loans. The findings indicate that simplified lawsuits are effective for uncomplicated cases with claims not exceeding five hundred million rupiah. This mechanism is not only time- and cost-efficient but also provides legal certainty for both parties. The legal consequence is a final and binding court decision that can be directly executed, thereby offering legal protection to the creditor and encouraging the debtor’s compliance with their obligations.